2016
DOI: 10.1007/s11999-016-4846-8
|View full text |Cite
|
Sign up to set email alerts
|

Can a Strategic Pipeline Initiative Increase the Number of Women and Underrepresented Minorities in Orthopaedic Surgery?

Abstract: BackgroundWomen and minorities remain underrepresented in orthopaedic surgery. In an attempt to increase the diversity of those entering the physician workforce, Nth Dimensions implemented a targeted pipeline curriculum that includes the Orthopaedic Summer Internship Program. The program exposes medical students to the specialty of orthopaedic surgery and equips students to be competitive applicants to orthopaedic surgery residency programs. The effect of this program on women and underrepresented minority app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
113
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(117 citation statements)
references
References 10 publications
0
113
1
3
Order By: Relevance
“… 15 , 42 Early exposure to surgical specialties through strategic support initiatives, such as summer internship programs, may help to describe these fields and establish mentorship relationships, which have been associated with significant increases in applicants who identify as URM. 13 , 14 Cochran et al 43 described a grounded theory model of successful mentorship in academic surgery that emphasizes the need for multiple mentors to engage with a diverse group of mentees over time, covering unique strategic domains as opposed to overreliance on fixed mentorship dyads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 42 Early exposure to surgical specialties through strategic support initiatives, such as summer internship programs, may help to describe these fields and establish mentorship relationships, which have been associated with significant increases in applicants who identify as URM. 13 , 14 Cochran et al 43 described a grounded theory model of successful mentorship in academic surgery that emphasizes the need for multiple mentors to engage with a diverse group of mentees over time, covering unique strategic domains as opposed to overreliance on fixed mentorship dyads.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 8 , 9 , 10 In response, surgical training programs across the US have engaged in initiatives aimed at increasing the number of individuals underrepresented in medicine (URM) based on the definition by the Association of American Medical Colleges (AAMC) as “those racial and ethnic populations that are underrepresented in the medical profession relative to their numbers in the general population.” 11 However, the impact of these efforts remains unclear. 12 , 13 , 14 , 15 This study used data from the AAMC to assess trends in the race/ethnicity of applicants and matriculants to surgical specialties between 2010 and 2018.…”
Section: Introductionmentioning
confidence: 99%
“…A single-institution study demonstrated that the application rate for minority students doubled after the introduction of a mandatory third-year musculoskeletal medicine rotation 7 . A survey of all U.S. medical schools demonstrated a 35% increase in the rate of application to orthopaedic programs among minorities following the institution of dedicated coursework in musculoskeletal medicine 8 .…”
mentioning
confidence: 99%
“…26 35 These programmes have shown that exposure to the realities of orthopaedic surgery served to improve the negative perceptions that medical students had of orthopaedic surgery as a profession 26 and resulted in improved female applications to orthopaedic residency with an odds ratio of up to 66. 35 Implicit or unconscious bias, encompasses the attitudes and perceptions that people have towards other people, and exists outside of conscious knowledge. Implicit bias negatively affects all aspects of women's orthopaedic surgery careers and has been implicated in the challenge of attracting women to orthopaedic surgery, optimising career development for women, gender pay inequities, and the lack of leadership opportunities for women.…”
Section: Original Articlementioning
confidence: 99%